2017
DOI: 10.1007/s00262-017-2030-y
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of ipilimumab plus temozolomide in patients with metastatic melanoma

Abstract: Checkpoint blockade has revolutionized the treatment of melanoma; however, it benefits only the minority of patients. Several agents have been combined with immunotherapy to improve T-cell activation and persistence including growth factor, chemotherapy, and radiation. Preclinical data suggest temozolomide, which metabolizes to the same active compound as dacarbazine, selectively depletes regulatory T cells. This potential immunomodulatory effect of temozolomide provides rationale for combination with ipilimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Although the exact mechanism has not been clearly elucidated, this synergistic dose-limiting toxicity is a cautionary note for immuno-oncology combinations. Interestingly, data presented at the 2014 American Society of Clinical Oncology (ASCO) annual meeting showed that a combination of ipilimumab with temozolomide (a drug similar in structure to dacarbazine) did not have such a high rate of dose-limiting liver toxicity, as unlike dacarbazine, temozolomide is not metabolized by the liver 118 .…”
Section: Stereotactic Radiotherapymentioning
confidence: 95%
“…Although the exact mechanism has not been clearly elucidated, this synergistic dose-limiting toxicity is a cautionary note for immuno-oncology combinations. Interestingly, data presented at the 2014 American Society of Clinical Oncology (ASCO) annual meeting showed that a combination of ipilimumab with temozolomide (a drug similar in structure to dacarbazine) did not have such a high rate of dose-limiting liver toxicity, as unlike dacarbazine, temozolomide is not metabolized by the liver 118 .…”
Section: Stereotactic Radiotherapymentioning
confidence: 95%
“…Accordingly, a combination strategy has been tried to improve the outcome, such as using chemotherapy and targeted therapies to increase tumor-specific antigen release and presentation [56]. So far, the combination of checkpoint blockade and TMZ therapy has yielded a promising anti-tumor efficacy in experimental models and clinical trials [57,58]. However, unlike vemurafenib, which reduces tumor-associated inflammation [50], TMZ not only enhances inflammatory response as observed in our current study but also promotes immune escape by upregulating PD-L1/L2 expression and reducing lymphocyte infiltration [57,59], thus potentially favoring a therapeutic response to immunotherapy [60].…”
mentioning
confidence: 99%
“…Therefore, the immune checkpoint inhibitor was continued up to 14 months, obtaining durable stable disease and good quality of life. A final severe encephalic progression, uselessly treated with temozolomide and re‐challenging ipilimumab, caused patient's death after 3 years from the first‐line therapy. In our experience, selected patients with BRAF‐mutated melanoma and without imminent risk of death can be suitably treated with up‐front immunotherapy followed by targeted therapy.…”
Section: Discussionmentioning
confidence: 99%